Investigation of Human Intrathecal Solute Transport Dynamics Using a Novel in vitro Cerebrospinal Fluid System Analog - Seiner, Akari; Burla, Goutham Kumar Reddy; Shrestha, Dev; Bowen, Mayumi; Horvath, Joshua D.; Martin, Bryn A. (Frontiers in Neuroimaging, 2022)
Background: Understanding the relationship between cerebrospinal fluid (CSF) dynamics and intrathecal drug delivery (ITDD) injection parameters is essential to improve treatment of central nervous system (CNS) disorders. Methods: An anatomically detailed in vitro model of the complete CSF system was constructed. Patient-specific cardiac- and respiratory-induced CSF oscillations were input to the model in the subarachnoid space and within the ventricles. CSF production was input at the lateral ventricles and CSF absorption at the superior sagittal sinus. A model small molecule simulated drug product containing fluorescein was imaged within the system over a period of three hours post-lumbar ITDD injections and used to quantify the impact of a) bolus injection volume and rate, b) post-injection flush volume, rate, and timing, c) injection location, and d) type of injection device. For each experiment, neuraxial distribution of fluorescein in terms of spatial temporal concentration, area-under-the-curve (AUC), and percent of injected dose (%ID) to the brain was quantified at a time point three-hours post-injection. Results: For all experiments conducted with ITDD administration in the lumbar spine, %ID to the brain did not exceed 11.6% at a time point three-hours post-injection. Addition of a 12 mL flush slightly increased solute transport to the brain up to +3.9 %ID compared to without a flush (p<0.01). Implantation of a lumbar catheter with the tip at an equivalent location to the lumbar placed needle, but with rostral tip orientation, resulted in a small improvement of 1.5 %ID to the brain (p<0.05). An increase of bolus volume from 5 mL to 20 mL improved solute transport to the brain from 5.0 to 6.3 %ID, but this improvement was not statistically significant. Increasing bolus injection rate from 5 mL/min to 13.3 mL/min lacked improvement of solute transport to the brain, with a value of 6.3 compared to 5.7 %ID. Conclusion: The in vitro modeling approach allowed precisely controlled and repeatable parametric investigation of ITDD injection protocols and devices. In combination, the results predict that parametric changes in lumbar spine ITDD-injection related parameters and devices can alter %ID to the brain and be tuned to optimize therapeutic benefit to CNS targets.